An analysis of Pakistan’s destination attributes and their effects on international tourists’ intentions to visit - Rauf, Abdul; de Oliveira Menezes, Vanessa; Jawaid, Waleed (Turyzm/Tourism, 2024)
This paper aims to generate a clear understanding of Pakistan’s important attributes and their direct and indirect influence via perceived destination images on international tourists’ intentions to visit for a holiday. It employed quantitative research methods through the use of a correlation research design. Both direct and indirect effects of destination attributes on visit intentions were examined and a self-administered online survey was distributed across several social media platforms. The results of multiple regression analysis revealed that landscape, services, local attitudes toward tourists, safety and risk, sport and special events were found to be statistically significant predictors of such intentions. However, all the destination attributes were found to have an indirect influence on international tourists via the perceived destination image of Pakistan.